Immune interventions in stroke - Fu, Ying (Nat Rev Neurol, 2015)
Inflammatory and immune responses in the brain can shape the clinical presentation and outcome of stroke. Approaches for effective management of acute stroke are sparse and many measures for brain protection fail, but our ability to modulate the immune system and modify the disease progression of multiple sclerosis is increasing. As a result, immune interventions are currently being explored as therapeutic interventions in acute stroke. In this Review, we compare the immunological features of acute stroke with those of multiple sclerosis, identify unique immunological features of stroke, and consider the evidence for immune interventions. In acute stroke, microglia activation and cell death products trigger an inflammatory cascade that damages vessels and the parenchyma within minutes to hours of the ischaemia or haemorrhage. Immune interventions that restrict brain inflammation, vascular permeability and tissue oedema must be administered rapidly to reduce acute immune-mediated destruction and to avoid subsequent immunosuppression. Preliminary results suggest that the use of drugs that modify disease in multiple sclerosis might accomplish these goals in ischaemic and haemorrhagic stroke. Further elucidation of the immune mechanisms involved in stroke is likely to lead to successful immune interventions.